2018
DOI: 10.4067/s0718-221x2018005003901
|View full text |Cite
|
Sign up to set email alerts
|

Planting density effect on some properties of Schizolobium parahyba wood

Abstract: This study aims to understand the effect of the initial planting density on the anatomical variability and basic wood density of Schizolobium parahyba var. amazonicum in a planted forest in Amazonia. The effect of the initial planting density on the radial variation from pith to bark of anatomy and basic density was evaluated. There were two planting densities, planting density-I (624 trees ha-1) and planting density-II (312 trees ha-1). Planting density significantly affected only the ray height, fiber length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Wood density had a weak and positive correlation with poplar growth traits within each planting density. Similar results with no significant effect of initial plantation density on wood's basic density were presented by Melo et al [10] and Cassidy et al [11]. A negative relationship between wood density and initial plantation density was found for Hevea brasiliensis by Naji et al [5].…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Wood density had a weak and positive correlation with poplar growth traits within each planting density. Similar results with no significant effect of initial plantation density on wood's basic density were presented by Melo et al [10] and Cassidy et al [11]. A negative relationship between wood density and initial plantation density was found for Hevea brasiliensis by Naji et al [5].…”
Section: Introductionsupporting
confidence: 80%
“…Research literature contains extensive discussion on the issue of stand density optimisation, which is utterly important from a practical standpoint. The multifaceted nature of the problem and a wide range of possible solutions account for why it has not lost its relevance [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Tropical species such as Anadenanthera peregrina, Ochroma pyramidale, and Schizolobium parahyba Var amazonicum showed the same type of increasing radial variation from pith to bark as J. copaia (Rueda and Williamson, 1992;Valente et al, 2013;Lobão et al, 2012) and the same behavior was found in tropical forest plantation species such as Guazuma crinita, Schizolobium parahyba, Tectona grandis, Toona ciliata, (Chavesta et al, 2020;Lima et al, 2021;Melo et al, 2018;Ribeiro et al, 2011). On the other hand, the tropical species Cariniana legalis also did not present any significant trend of radial variation in the pith-bark direction, the same as the species H. crepitans (Lima et al, 2011;Ribeiro et al, 2011), which does not exist a significant difference in the radial variation of wood in the species H. crepitans is favorable for industrial transformation processes (Plaster et al, 2008;Rios et al, 2018).…”
Section: Discussionmentioning
confidence: 71%
“…Higher planting densities in poplar plantations achieve increased biomass with almost the same wood quality obtainable with lower densities based on our results. Contrasting results may be due to differences between species, environmental conditions, and the planting density tested [13]. For the fiber properties, the variation of FL within a planting density is controversial in woody species.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al [12] reported that the planting density influence on growth traits and wood properties is greater than that of the wood chemical composition. Research on guapuruvu [13] showed that planting density only significantly affected the fiber length (FL) and fiber wall thickness. Therefore, the initial planting density choice is crucial to maximize growth rate and optimize wood quality.…”
Section: Introductionmentioning
confidence: 99%